COVID-19-Associated Ischemic Colitis: A Rare Manifestation of COVID-19 Infection—Case Report and Review. (March 2022) - Uhlenhopp, Dustin J.; Ramachandran, Rajarajeshwari; Then, Eric; Parvataneni, Swetha; Grantham, Tyler; Gaduputi, Vinaya
Following the first report of COVID-19 infection in December 2019 as a respiratory illness, it has proven to be a multisystem disease. There are few reported cases of ischemic colitis with COVID-19 infection in the medical literature to date and we have limited understanding of its pathophysiology. We report 2 cases of ischemic colitis as the only manifestation of COVID-19. In addition, we review the current limited literature regarding COVID-19-associated ischemic colitis.